Exploration and Characterization of Trichoderma sp. in Conventional and Organic Rice field in Bali - A. A. S. P. R. Andriani; Idris Sharif; Bohari M Yamin; S. A. M. P. Suryani; Krisnawan Kalimutu (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2021)
Abstract. Although Trichoderma spp has been widely used in the SRI technique of rice cultivation the sources of Trichoderma that can adapt well to the local environment have been an interesting issue for quite some time. It is commonly agreed that the local Trichoderma is much more preferred to be used for rice cultivation. In the present study, the Trichoderma from the soil of a rice field in Sukawati District, Bali where conventional fertilizer and pesticide has been applied for a very long time was isolated. After macroscopic observations (green color and sweet coconut smell ) the single isolated fungi have very much resembled Trichoderma Harzianum. 2 mL of the Trichoderma Harzianum solution was introduced in a plastic container containing 200 g half-boiled rice. After seven days the rice in the plastic appeared green. This sample will be used to produce more T. Harzianum for rice cultivation. One of the T.Harzianum treated rice hosts was coated with gold and subjected to SEM observation. Very high populated T. Harzianum fungi were observed. It was dominated by hyphae. No conidia and conidiophores were spotted. Instead, quite a high density of spherical and oval shape spores was observed. Such a high density of T.Harzianum will certainly meet the requirement for an efficient application in the cultivation field. It would also be interesting to see the interaction between such a highly populated T.Harzianum with other fungi or pathogens in understanding the role of Trichoderma as an antipathogen